Dilemas práticos: uma analogia entre dilemas morais e jurídicos - Ghidolin, Clodoveo (2015)
The central scope in this doctoral thesis refers to the comparative analysis of dilemmas in moral and legal cases in order to sustain that, genuinely moral dilemmas and genuinely legal dilemmas do not exist. Moreover, those examples which frequently are used and referred to in literature or are part of distinct systems of rules, or are mental creations which serve to evaluate or analyze a system of rules, or yet are false dilemmas (pseudo dilemmas) and, therefore, are perfectly solvable. Thus, we analyze, in Law, the arguments that lead to the classification and ruling of legal cases (in easy, difficult and tragic) and compared them with the arguments involved in moral dilemmas. We assessed whether these cases are real or just ideal, that is, if moral and legal dilemmas indeed exist. We have performed a historical overview on the influence of the main paradigm related to the theme, namely, Legal Positivism and we have presented logical problems (coherence and completeness) of the legal ruling, especially the emergence of gaps. As we have approached the theme of gaps from the vagueness of legal terms and presented the classification and solution of legal cases from Dworkin, Hart, Atienza and MacCormick. Within moral scope, we present a historical overview of the traditional view of moral problems, the interdependence between Moral and Law, we investigate the existence of moral dilemmas of soluble and insoluble type, we expose the problem of decidability of moral cases and present a taxonomy and solution to moral issues in easy, difficult and tragic (dilemmas). Eventually, we developed a comparative table with the four components of moral and legal decisions: on the deliberator, on the object of deliberation, on the decision-making process, and on the result of the deliberation. Forthwith, we describe each of the criteria related to the deliberation components in order to present points of approximation, the differences and connections that may exist among themselves.